Impact of inclusive leadership on employees’ innovative behavior: A relational silence approach - Wu, Guo-feng; Li, Mei (Frontiers in Psychology, 2023)
Although employees' silence is a common phenomenon in organizations, the mediating role of relational silence has not been studied in inclusive leadership and innovative behavior. In this study, based on the theory of social exchange, relational silence is used as a mediating variable to explore the internal mechanisms of inclusive leadership on employees' innovative behavior. Data from 263 in-service leaders and employees were collected using convenience sampling and analyzed using Amos and SPSS statistical software package via questionnaires distributed to companies in six cities in the Guangdong province of China. The results showed that inclusive leadership has a significant positive predictive effect on employees' innovative behavior(β=0.590, P﹤0.01), while inclusive leadership is negative and significantly correlated with relational silence(β=-0.469, P﹤0.01). More so, relational silence has a significant negative correlation with employees' innovative behavior(β=-0.408, P﹤0.01), and relational silence partially mediates the relationship between inclusive leadership and employee innovation behavior. The mediating role of relational silence between inclusive leadership and employees' innovative behavior is revealed for the first time, theoretically broadening and enriching the connotation of inclusive leadership's influence mechanism on employees' innovative behavior and providing new ideas in practice for constructing inclusive leadership styles, reducing the incidence of relational silence, and evoking employees' innovative behavior.